Herbal coating with lasting bacteriostasis function
Patent Information
- Application Number
- CN202510105153.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-04-15
Smart Images

Figure BDA0005255227480000101
Abstract
Description
Technical Field
[0001] The present application relates to the field of coating technology, and in particular to a long-lasting antibacterial herbal coating. Background Art
[0002] Common antibacterial coatings on the market generally use organic antibacterial agents or inorganic silver ion antibacterial agents. Organic antibacterial agents are sensitive to pH, have large addition amounts, are relatively toxic, and are irritating to humans and animals. A large number of Chinese herbal medicines are known to have antibacterial effects. Therefore, combining traditional Chinese herbal medicines with coatings to prepare Chinese herbal antibacterial coatings is a very valuable research direction.
[0003] In the prior art, antibacterial coatings are prepared by simply crushing antibacterial Chinese herbal medicines such as mugwort and artemisia annua into fine particles and mixing them with coatings. However, the release of the antibacterial Chinese herbal ingredients cannot be controlled. After the paint film is dried, the effective antibacterial ingredients in it can easily and quickly evaporate into the air, and then lose the antibacterial effect after a short time. Summary of the invention
[0004] In order to improve the long-lasting antibacterial property of the coating, the present application provides a long-lasting antibacterial herbal coating.
[0005] The present application provides a durable antibacterial herbal coating, which adopts the following technical solution: A durable antibacterial herbal paint, comprising the following raw materials in parts by weight: 40-50 parts of epoxy resin, 18-22 parts of kaolin, 8-13 parts of Chinese herbal antibacterial agent, 0.4-1.2 parts of dimethyl silicone oil, 0.8-1.4 parts of polyamide, 0.6-1.6 parts of hydroxyethyl cellulose, and 48-64 parts of ethyl acetate; The preparation method of the Chinese herbal medicine antibacterial agent comprises the following steps: β-cyclodextrin is added into deionized water, heated and stirred, then wormwood essential oil is added, stirred evenly, cooled and freeze-dried to prepare a Chinese herbal antibacterial agent.
[0006] By adopting the above technical scheme, wormwood essential oil has antibacterial activity, but wormwood essential oil is easy to volatilize at room temperature, which can easily lead to a decrease in antibacterial effect. Therefore, wormwood essential oil is wrapped by β-cyclodextrin, and water molecules push the essential oil into the cavity of cyclodextrin to produce a complex and form a stable packaging structure, thereby playing a sustained-release antibacterial role.
[0007] In addition, β-cyclodextrin can adsorb formaldehyde through its unique hydrophobic cavity structure, thus having a good adsorption effect on formaldehyde.
[0008] In addition, through the defoaming effect of dimethyl silicone oil in the system, the curing effect of polyamide in the system, and the thickening effect of hydroxyethyl cellulose in the system, the coating has better stability, which is more helpful to improve the sustained-release antibacterial effect of the coating and the formaldehyde adsorption effect.
[0009] Preferably, the mass ratio of the wormwood essential oil to β-cyclodextrin is 1:(0.16-0.24).
[0010] By adopting the above technical solution, the mass ratio of wormwood essential oil and β-cyclodextrin is controlled within the above range, which can effectively improve the packaging effect of β-cyclodextrin on wormwood essential oil.
[0011] Preferably, the composition further comprises 11-15 parts of porous starch, wherein the preparation method of the porous starch comprises the following steps: S1, adding corn starch to a sodium chloride solution, heating and stirring evenly, adding sodium hydroxide solution to adjust the pH to 11, continuing to stir, then adding sodium trimetaphosphate and sodium hydrogen phosphate, continuing to stir, and then adjusting the pH to neutral with a hydrochloric acid solution, followed by washing, filtering, drying, and grinding to obtain sodium trimetaphosphate cross-linked corn starch; S2. Add sodium trimetaphosphate cross-linked corn starch into disodium hydrogen phosphate-citric acid buffer, preheat at a constant temperature, then add amylase to react, and finally add sodium hydroxide solution until the reaction becomes neutral. After terminating the reaction, wash and dry to obtain porous starch.
[0012] By adopting the above technical scheme, the corn starch is cross-linked with trimetaphosphoric acid, so that the cross-linked corn starch forms a macromolecule with a network structure, which improves the strength and stability of the corn starch. The amylase is then absorbed into the surface of the cross-linked corn starch, thereby corroding and degrading the cross-linked corn starch, so that the cross-linked corn starch is corroded and etched into a porous structure, so that the inclusion complex formed by wormwood essential oil and β-cyclodextrin enters the pore size of the porous starch by adsorption, further improving the stability of the Chinese herbal antibacterial agent in the coating, and further improving the antibacterial sustained-release effect of the Chinese herbal medicine.
[0013] Moreover, porous starch, through its porous structure and high specific surface area, can not only adsorb and immobilize microorganisms, but also has a good adsorption effect on formaldehyde, thus having good antibacterial and formaldehyde adsorption effects.
[0014] Preferably, the mass ratio of corn starch, sodium trimetaphosphate and amylase is 1:(0.12-0.16):0.02.
[0015] By adopting the above technical solution, the mass ratio of corn starch, sodium trimetaphosphate and amylase is controlled within the above range, which has a positive effect on improving the antibacterial sustained-release effect of Chinese herbal medicine.
[0016] Preferably, titanium dioxide is further added during the preparation of the porous starch. The preparation method of the porous starch comprises the following steps: S1, adding corn starch to a sodium chloride solution, heating and stirring evenly, adding sodium hydroxide solution to adjust the pH to 11, continuing to stir, then adding sodium trimetaphosphate and sodium hydrogen phosphate, continuing to stir, and then adjusting the pH to neutral with a hydrochloric acid solution, followed by washing, filtering, drying, and grinding to obtain sodium trimetaphosphate cross-linked corn starch; S2, adding sodium metaphosphate cross-linked corn starch into disodium hydrogen phosphate-citric acid buffer, preheating at a constant temperature, then adding amylase to react, and finally adding sodium hydroxide solution until the reaction is neutral, terminating the reaction, washing and drying, and obtaining primary porous starch; S3. Add a surfactant to deionized water, stir evenly, add titanium dioxide and porous starch, mix thoroughly, filter and dry in sequence to obtain porous starch.
[0017] By adopting the above technical scheme, the surfactant can improve the interaction between titanium dioxide and porous starch, promote the uniform distribution of titanium dioxide on the surface of porous starch, so that titanium dioxide is loaded on the porous starch. Due to its own porous structure, the porous starch has good adsorption capacity for formaldehyde, and titanium dioxide, as a photocatalytic degradation material, has the characteristics of high photocatalytic activity and has a degradation effect on formaldehyde.
[0018] Titanium dioxide has a good antibacterial effect. Through the effective combination of titanium dioxide, porous starch and mugwort essential oil, the antibacterial property of the coating can be further improved.
[0019] Therefore, titanium dioxide is loaded on porous starch, and the strong adsorption of porous starch on formaldehyde is utilized to promote the degradation of formaldehyde. At the same time, it also improves the stability of titanium dioxide in the coating, effectively improving the long-lasting antibacterial properties of titanium dioxide.
[0020] Preferably, the mass ratio of the primary porous starch to titanium dioxide is 1:(0.2-0.4).
[0021] By adopting the above technical solution, the mass ratio of primary porous starch and titanium dioxide is controlled within the above range, which effectively improves the degradation effect of the coating on formaldehyde.
[0022] Preferably, the surfactant is sodium dodecyl sulfate.
[0023] Preferably, the titanium dioxide is prepared by modification, and the modification preparation method of the titanium dioxide comprises the following steps: The carbon nanotubes are added into a mixed solution of anhydrous ethanol and deionized water, and after being fully stirred, titanium dioxide is added, and then the solution is allowed to stand and age, and then dried and calcined to obtain modified titanium dioxide.
[0024] By adopting the above technical solution, carbon nanotubes are infiltrated into titanium dioxide, the utilization rate of photogenerated electron-hole pairs is increased, the recombination of photogenerated electron-hole pairs is effectively reduced, the photocatalytic activity of titanium dioxide is improved, and thus the degradation effect of titanium dioxide on formaldehyde is improved.
[0025] Moreover, carbon nanotubes can physically adsorb bacteria on their surface, thereby limiting the activity and reproduction of bacteria. In addition, carbon nanotubes can also react chemically with bacteria to kill them. Therefore, the infiltration of carbon nanotubes into titanium dioxide not only improves the degradation of formaldehyde by titanium dioxide, but also improves the antibacterial effect of titanium dioxide.
[0026] Preferably, the mass ratio of titanium dioxide to carbon nanotubes is 1:(0.09-0.13).
[0027] By adopting the above technical solution, the mass ratio of titanium dioxide to carbon nanotubes is controlled within the above range, which can effectively improve the catalytic activity of titanium dioxide.
[0028] Preferably, a method for preparing a durable antibacterial herbal coating comprises the following steps: After the epoxy resin and ethyl acetate are evenly mixed, kaolin is added and stirring is continued. Then, the Chinese herbal antibacterial agent, dimethyl silicone oil, polyamide and hydroxyethyl cellulose are added and stirred evenly to obtain a durable antibacterial herbal coating.
[0029] In summary, the present application includes at least one of the following beneficial technical effects: 1. Mugwort essential oil has antibacterial activity, but it is easy to volatilize at room temperature, which can easily lead to a decrease in antibacterial effect. Therefore, the mugwort essential oil is encapsulated by β-cyclodextrin, and water molecules push the essential oil into the cavity of cyclodextrin to produce a complex and form a stable packaging structure, thereby playing a role of sustained-release antibacterial; β-cyclodextrin can adsorb formaldehyde through its unique hydrophobic cavity structure, thereby having a good adsorption effect on formaldehyde.
[0030] 2. First, the corn starch is cross-linked with trimetaphosphoric acid, and then the amylase is absorbed into the surface of the cross-linked corn starch, so that the cross-linked corn starch is eroded and etched into a porous structure, so that the inclusion compound formed by wormwood essential oil and cyclodextrin enters the pore size of the porous starch by adsorption, further improving the stability of the Chinese herbal medicine antibacterial agent in the coating, and further improving the antibacterial sustained-release effect of the Chinese herbal medicine. And the porous starch can not only adsorb and immobilize microorganisms through its porous structure and high specific surface area, but also has a good adsorption effect on formaldehyde, thereby having a good antibacterial effect and formaldehyde adsorption effect. DETAILED DESCRIPTION
[0031] The present application example discloses a long-lasting antibacterial herbal paint. The raw materials involved in the present application can be obtained from the market, and the epoxy resin is purchased from Jinan Chuangshi Chemical Co., Ltd. (CAS No.: 24969-06-0).
[0032] Example 1 The long-lasting antibacterial herbal paint includes the following raw materials by weight: 40g epoxy resin, 18g kaolin, 8g Chinese herbal antibacterial agent, 0.4g dimethyl silicone oil, 0.8g polyamide, 0.6g hydroxyethyl cellulose, and 48g ethyl acetate.
[0033] The preparation method of the Chinese herbal medicine antibacterial agent comprises the following steps: Add 10g of β-cyclodextrin to 100g of deionized water, stir in a magnetic stirrer at a constant temperature, set the temperature to 60°C, and the stirring speed to 400r / min, then add 1.6g of mugwort essential oil, stir for 3h, take out the solution and cool it at 25°C, cool it to a solid at -18°C, and then put it into a freeze dryer for freeze drying for 12h to obtain a Chinese herbal antibacterial agent.
[0034] The preparation method of the durable antibacterial herbal paint comprises the following steps: After the epoxy resin and ethyl acetate are evenly mixed, kaolin is added and stirring is continued. Then, the Chinese herbal antibacterial agent, dimethyl silicone oil, polyamide and hydroxyethyl cellulose are added and stirred evenly to obtain a durable antibacterial herbal coating.
[0035] Example 2 The long-lasting antibacterial herbal paint includes the following raw materials by weight: 50g epoxy resin, 22g kaolin, 13g Chinese herbal antibacterial agent, 1.2g dimethyl silicone oil, 1.4g polyamide, 1.6g hydroxyethyl cellulose, and 64g ethyl acetate.
[0036] The preparation method of the Chinese herbal medicine antibacterial agent comprises the following steps: Add 10g of β-cyclodextrin to 100g of deionized water, stir in a magnetic stirrer at a constant temperature, set the temperature to 60°C, and the stirring speed to 400r / min, then add 2.4g of mugwort essential oil, stir for 3h, take out the solution and cool it at 25°C, cool it to a solid at -18°C, and then put it into a freeze dryer for freeze drying for 12h to obtain a Chinese herbal antibacterial agent.
[0037] The preparation method of the durable antibacterial herbal paint comprises the following steps: After the epoxy resin and ethyl acetate are evenly mixed, kaolin is added and stirring is continued. Then, the Chinese herbal antibacterial agent, dimethyl silicone oil, polyamide and hydroxyethyl cellulose are added and stirred evenly to obtain a durable antibacterial herbal coating.
[0038] Example 3 The long-lasting antibacterial herbal paint includes the following raw materials by weight: 45g epoxy resin, 20g kaolin, 11g Chinese herbal antibacterial agent, 0.8g dimethyl silicone oil, 1.1g polyamide, 1.1g hydroxyethyl cellulose, and 56g ethyl acetate.
[0039] The preparation method of the Chinese herbal medicine antibacterial agent comprises the following steps: Add 10g of β-cyclodextrin to 100g of deionized water, stir in a magnetic stirrer at a constant temperature, set the temperature to 60°C, and the stirring speed to 400r / min, then add 2.0g of mugwort essential oil, stir for 3h, take out the solution and cool it at 25°C, cool it to a solid at -18°C, and then put it into a freeze dryer for freeze drying for 12h to obtain a Chinese herbal antibacterial agent.
[0040] The preparation method of the durable antibacterial herbal paint comprises the following steps: After the epoxy resin and ethyl acetate are evenly mixed, kaolin is added and stirring is continued. Then, the Chinese herbal antibacterial agent, dimethyl silicone oil, polyamide and hydroxyethyl cellulose are added and stirred evenly to obtain a durable antibacterial herbal coating.
[0041] Example 4 The difference between Example 4 and Example 3 is that the mass ratio of wormwood essential oil to β-cyclodextrin is 1:0.10.
[0042] Example 5 The difference between Example 5 and Example 3 is that the mass ratio of wormwood essential oil to β-cyclodextrin is 1:0.30.
[0043] Example 6 The difference between Example 6 and Example 3 is that 11 g of porous starch is further included.
[0044] The method for preparing porous starch comprises the following steps: S1. Add 100g corn starch to 1% (w / v) sodium chloride solution to prepare 40% starch milk, and adjust the pH to 11 with 1M sodium hydroxide solution, stir at 60°C for 30min, add 12g sodium trimetaphosphate and 30g sodium bicarbonate, continue heating and stirring at 60°C for 30min, and then adjust the pH to neutral with 1M hydrochloric acid solution, then wash three times with distilled water, filter to obtain a precipitate, dry the precipitate in a vacuum oven, dry at 60°C for 12h, and finally grind and sieve the dried product and seal it for storage to obtain sodium trimetaphosphate cross-linked corn starch; S2. Prepare 50 mL of disodium hydrogen phosphate-citric acid buffer with a pH of 4.6 (the amount of disodium hydrogen phosphate is 0.2 mol / L, and the amount of citric acid is 0.1 mol / L), add sodium trimetaphosphate cross-linked corn starch, preheat in a constant temperature water bath at 45°C for 10 min, then add 2 g of amylase, react in a constant temperature water bath at 45°C for 8 h, finally add 4% sodium hydroxide solution by mass until the reaction solution is neutral, terminate the reaction, wash the particles three times and then dry them in vacuum to obtain porous starch.
[0045] The amylase includes α-amylase and saccharifying enzyme, and the mass ratio of α-amylase to saccharifying enzyme is 1:4.
[0046] The preparation method of the durable antibacterial herbal paint comprises the following steps: After the epoxy resin and ethyl acetate are evenly mixed, kaolin is added and stirring is continued. Then, a Chinese herbal antibacterial agent, porous starch, dimethyl silicone oil, polyamide and hydroxyethyl cellulose are added and stirred evenly to obtain a durable antibacterial herbal coating.
[0047] Example 7 The difference between Example 7 and Example 6 is that 15 g of porous starch is further included.
[0048] The method for preparing porous starch comprises the following steps: S1. Add 100g corn starch to 1% (w / v) sodium chloride solution to prepare 40% starch milk, and adjust the pH to 11 with 1M sodium hydroxide solution, stir at 60°C for 30min, add 16g sodium trimetaphosphate and 30g sodium bicarbonate, continue heating and stirring at 60°C for 30min, and then adjust the pH to neutral with 1M hydrochloric acid solution, then wash three times with distilled water, filter to obtain a precipitate, dry the precipitate in a vacuum oven, dry at 60°C for 12h, and finally grind and sieve the dried product to seal and store to obtain sodium trimetaphosphate cross-linked corn starch; S2. Prepare 50 mL of disodium hydrogen phosphate-citric acid buffer with a pH of 4.6 (the amount of disodium hydrogen phosphate is 0.2 mol / L, and the amount of citric acid is 0.1 mol / L), add sodium trimetaphosphate cross-linked corn starch, preheat in a constant temperature water bath at 45°C for 10 min, then add 2 g of amylase, react in a constant temperature water bath at 45°C for 8 h, finally add 4% sodium hydroxide solution by mass until the reaction solution is neutral, terminate the reaction, wash the particles three times and then dry them in vacuum to obtain porous starch.
[0049] The amylase includes α-amylase and saccharifying enzyme, and the mass ratio of α-amylase to saccharifying enzyme is 1:4.
[0050] Example 8 The difference between Example 8 and Example 6 is that 13 g of porous starch is also included.
[0051] The method for preparing porous starch comprises the following steps: S1. Add 100g corn starch to 1% (w / v) sodium chloride solution to prepare 40% starch milk, adjust the pH to 11 with 1M sodium hydroxide solution, stir at 60°C for 30min, add 14g sodium trimetaphosphate and 30g sodium bicarbonate, continue heating and stirring at 60°C for 30min, and then adjust the pH to neutral with 1M hydrochloric acid solution, then wash three times with distilled water, filter to obtain a precipitate, dry the precipitate in a vacuum oven, dry at 60°C for 12h, and finally grind and sieve the dried product to seal and store to obtain sodium trimetaphosphate cross-linked corn starch; S2. Prepare 50 mL of disodium hydrogen phosphate-citric acid buffer with a pH of 4.6 (the amount of disodium hydrogen phosphate is 0.2 mol / L, and the amount of citric acid is 0.1 mol / L), add sodium trimetaphosphate cross-linked corn starch, preheat in a constant temperature water bath at 45°C for 10 min, then add 2 g of amylase, react in a constant temperature water bath at 45°C for 8 h, finally add 4% sodium hydroxide solution by mass until the reaction solution is neutral, terminate the reaction, wash the particles three times and then dry them in vacuum to obtain porous starch.
[0052] The amylase includes α-amylase and saccharifying enzyme, and the mass ratio of α-amylase to saccharifying enzyme is 1:4.
[0053] Example 9 The difference between Example 9 and Example 8 is that the mass ratio of corn starch, sodium trimetaphosphate and amylase is 1:0.08:0.02.
[0054] Example 10 The difference between Example 10 and Example 8 is that the mass ratio of corn starch, sodium trimetaphosphate and amylase is 1:0.20:0.02.
[0055] Embodiment 11 The difference between Example 11 and Example 8 is that titanium dioxide is further added during the preparation of porous starch. The preparation method of porous starch comprises the following steps: S1. Add 100g corn starch to 1% (w / v) sodium chloride solution to prepare 40% starch milk, adjust the pH to 11 with 1M sodium hydroxide solution, stir at 60°C for 30min, add 14g sodium trimetaphosphate and 30g sodium bicarbonate, continue heating and stirring at 60°C for 30min, and then adjust the pH to neutral with 1M hydrochloric acid solution, then wash three times with distilled water, filter to obtain a precipitate, dry the precipitate in a vacuum oven, dry at 60°C for 12h, and finally grind and sieve the dried product to seal and store to obtain sodium trimetaphosphate cross-linked corn starch; S2, prepare 50mL of disodium hydrogen phosphate-citric acid buffer solution with a pH of 4.6 (wherein the amount of disodium hydrogen phosphate is 0.2mol / L, and the amount of citric acid is 0.1mol / L), then add sodium trimetaphosphate cross-linked corn starch, preheat in a 45°C constant temperature water bath for 10min, then add 2g of amylase, react in a 45°C constant temperature water bath for 8h, finally add a 4% sodium hydroxide solution by mass until the reaction solution is neutral, terminate the reaction, wash the particles three times and then dry them in vacuum to obtain a primary porous material: S3. Add 2 g of surfactant to 50 g of deionized water, stir thoroughly, then add 2 g of titanium dioxide and 10 g of primary porous starch, stir at 80 r / min at 30°C with a constant temperature magnetic stirrer for 6 h, then filter, and dry the resulting precipitate at 40°C for 4 h to obtain porous starch.
[0056] The surfactant is sodium dodecyl sulfate.
[0057] Example 12 The difference between Example 12 and Example 8 is that titanium dioxide is further added during the preparation of porous starch. The preparation method of porous starch comprises the following steps: S1. Add 100g corn starch to 1% (w / v) sodium chloride solution to prepare 40% starch milk, adjust the pH to 11 with 1M sodium hydroxide solution, stir at 60°C for 30min, add 14g sodium trimetaphosphate and 30g sodium bicarbonate, continue heating and stirring at 60°C for 30min, and then adjust the pH to neutral with 1M hydrochloric acid solution, then wash three times with distilled water, filter to obtain a precipitate, dry the precipitate in a vacuum oven, dry at 60°C for 12h, and finally grind and sieve the dried product to seal and store to obtain sodium trimetaphosphate cross-linked corn starch; S2, prepare 50mL of disodium hydrogen phosphate-citric acid buffer solution with a pH of 4.6 (wherein the amount of disodium hydrogen phosphate is 0.2mol / L, and the amount of citric acid is 0.1mol / L), then add sodium trimetaphosphate cross-linked corn starch, preheat in a 45°C constant temperature water bath for 10min, then add 2g of amylase, react in a 45°C constant temperature water bath for 8h, finally add a 4% sodium hydroxide solution by mass until the reaction solution is neutral, terminate the reaction, wash the particles three times and then dry them in vacuum to obtain a primary porous material: S3. Add 4 g of surfactant to 50 g of deionized water, stir thoroughly, then add 4 g of titanium dioxide and 10 g of primary porous starch, stir at 80 r / min at 30°C with a constant temperature magnetic stirrer for 6 h, then filter, and dry the resulting precipitate at 40°C for 4 h to obtain porous starch.
[0058] The surfactant is sodium dodecyl sulfate.
[0059] Embodiment 13 The difference between Example 13 and Example 8 is that titanium dioxide is further added during the preparation of porous starch. The preparation method of porous starch comprises the following steps: S1. Add 100g corn starch to 1% (w / v) sodium chloride solution to prepare 40% starch milk, adjust the pH to 11 with 1M sodium hydroxide solution, stir at 60°C for 30min, add 14g sodium trimetaphosphate and 30g sodium bicarbonate, continue heating and stirring at 60°C for 30min, and then adjust the pH to neutral with 1M hydrochloric acid solution, then wash three times with distilled water, filter to obtain a precipitate, dry the precipitate in a vacuum oven, dry at 60°C for 12h, and finally grind and sieve the dried product to seal and store to obtain sodium trimetaphosphate cross-linked corn starch; S2, prepare 50mL of disodium hydrogen phosphate-citric acid buffer solution with a pH of 4.6 (wherein the amount of disodium hydrogen phosphate is 0.2mol / L, and the amount of citric acid is 0.1mol / L), then add sodium trimetaphosphate cross-linked corn starch, preheat in a 45°C constant temperature water bath for 10min, then add 2g of amylase, react in a 45°C constant temperature water bath for 8h, finally add a 4% sodium hydroxide solution by mass until the reaction solution is neutral, terminate the reaction, wash the particles three times and then dry them in vacuum to obtain a primary porous material: S3. Add 3g of surfactant to 50g of deionized water, stir thoroughly, then add 3g of titanium dioxide and 10g of primary porous starch, stir at 80r / min at 30°C with a constant temperature magnetic stirrer for 6h, then filter, and dry the resulting precipitate at 40°C for 4h to obtain porous starch.
[0060] The surfactant is sodium dodecyl sulfate.
[0061] Embodiment 14 The difference between Example 14 and Example 13 is that the mass ratio of primary porous starch to titanium dioxide is 1:0.1.
[0062] Embodiment 15 The difference between Example 15 and Example 13 is that the mass ratio of primary porous starch to titanium dioxide is 1:0.5.
[0063] Example 16 The difference between Example 16 and Example 13 is that the titanium dioxide is prepared by modification, and the modification preparation method of titanium dioxide comprises the following steps: 0.09g of carbon nanotubes were added to a mixed solution of 7g of anhydrous ethanol and 10g of deionized water, and then fully dispersed by ultrasonic oscillation, and then 1g of titanium dioxide was added, followed by standing and aging for 24 hours. The obtained gel was dried in a hot air drying oven at 100°C for 2 hours, and calcined in a muffle furnace for 2 hours to obtain modified titanium dioxide.
[0064] Embodiment 17 The difference between Example 17 and Example 13 is that the titanium dioxide is prepared by modification, and the modification preparation method of titanium dioxide comprises the following steps: 0.13g of carbon nanotubes were added to a mixed solution of 7g of anhydrous ethanol and 10g of deionized water, and then fully dispersed by ultrasonic oscillation, and then 1g of titanium dioxide was added, followed by standing and aging for 24 hours. The obtained gel was dried in a hot air drying oven at 100°C for 2 hours, and calcined in a muffle furnace for 2 hours to obtain modified titanium dioxide.
[0065] Embodiment 18 The difference between Example 18 and Example 13 is that the titanium dioxide is prepared by modification, and the modification preparation method of titanium dioxide comprises the following steps: 0.11g of carbon nanotubes were added to a mixed solution of 7g of anhydrous ethanol and 10g of deionized water, and then fully dispersed by ultrasonic oscillation, and then 1g of titanium dioxide was added, followed by standing and aging for 24 hours. The obtained gel was dried in a hot air drying oven at 100°C for 2 hours, and calcined in a muffle furnace for 2 hours to obtain modified titanium dioxide.
[0066] Embodiment 19 The difference between Example 19 and Example 18 is that the mass ratio of titanium dioxide to carbon nanotubes is 1:0.05.
[0067] Embodiment 20 The difference between Example 20 and Example 18 is that the mass ratio of titanium dioxide to carbon nanotubes is 1:0.17.
[0068] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that the Chinese herbal antibacterial agent is only wormwood essential oil.
[0069] Performance testing: The durable antibacterial herbal coatings prepared in Examples 1-20 and Comparative Example 1 were coated on the surface of a transparent ABS resin plate using an air spraying process to form a 20 μm thick coating, which was then dried for one week at room temperature and a relative humidity of 60%. The performance of each coating was then tested and the test results are recorded in Table 1.
[0070] 1. Antibacterial properties The bacterial solution was applied on the coating surface and cultured for 24±1 hours at 35±1°C with a relative humidity of not less than 90%. The bacterial solution was then rinsed clean and the antibacterial performance and antibacterial durability tests were conducted using Escherichia coli (ATCC8739) with reference to GB / T21866-2008 "Determination of antibacterial properties and antibacterial effects of antibacterial coatings (paint films)".
[0071] 2. Formaldehyde adsorption The coated product is placed in a confined space and formaldehyde is injected, with the initial formaldehyde concentration being 15 mg / m 3 After 48 hours of placement, the test was carried out using the method in "JCT10742008 Purification Performance of Indoor Air Purification Functional Coating Materials".
[0072] Data Analysis: Specifically combining the test results of Examples 6-8 and Example 3, the antibacterial properties, persistent antibacterial properties, and formaldehyde adsorption of Examples 6-8 are better than those of Example 3. The analysis is as follows: the difference between Examples 6-8 and Example 3 is that the coating also contains porous starch, which has a porous structure and a high specific surface area. It can not only absorb the inclusion complex formed by wormwood essential oil and β-cyclodextrin into the pore size of the porous starch, but also effectively absorb formaldehyde and inhibit bacterial growth, thereby making the coating have better antibacterial properties, persistent antibacterial properties, and formaldehyde adsorption.
[0073] Specifically combining the test results of Examples 11-13 and Example 8, the antibacterial property, persistent antibacterial property, and formaldehyde adsorption of Examples 11-13 are better than those of Example 8. The analysis is as follows: the difference between Examples 11-13 and Example 8 is that: they also contain titanium dioxide, and the titanium dioxide is loaded on the porous starch. Through the antibacterial property and photocatalytic activity of titanium dioxide, not only the growth of antibacterial bacteria can be inhibited, but also the degradation of formaldehyde can be promoted, so that the coating has better antibacterial property, persistent antibacterial property, and formaldehyde adsorption.
[0074] Specifically combining the test results of Examples 16-18 and Example 13, the antibacterial properties, persistent antibacterial properties, and formaldehyde adsorption of Examples 16-18 are better than those of Example 13. The analysis is as follows: the difference between Examples 16-18 and Example 13 is that the infiltration of carbon nanotubes into titanium dioxide not only improves the degradation of formaldehyde by titanium dioxide, but also improves the antibacterial properties of titanium dioxide through the antibacterial effect of carbon nanotubes, thereby making the coating have better antibacterial properties, persistent antibacterial properties, and formaldehyde adsorption.
[0075] Specifically combining the test results of Example 3 and Comparative Example 1, the antibacterial property, persistent antibacterial property and formaldehyde adsorption of Example 3 are better than those of Comparative Example 1. The analysis is as follows: the difference between Example 3 and Comparative Example 1 is that the wormwood essential oil is wrapped by β-cyclodextrin to form a stable package and structure, thereby achieving a sustained-release antibacterial effect, and β-cyclodextrin has a good adsorption effect on formaldehyde, so that the coating has better antibacterial property, persistent antibacterial property and formaldehyde adsorption.
[0076] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.
Claims
1. A long-lasting antibacterial herbal paint, characterized in that: The invention comprises the following raw materials in parts by weight: 40-50 parts of epoxy resin, 18-22 parts of kaolin, 8-13 parts of Chinese herbal antibacterial agent, 0.4-1.2 parts of dimethyl silicone oil, 0.8-1.4 parts of polyamide, 0.6-1.6 parts of hydroxyethyl cellulose, and 48-64 parts of ethyl acetate; The preparation method of the Chinese herbal medicine antibacterial agent comprises the following steps: β-cyclodextrin is added into deionized water, heated and stirred, then wormwood essential oil is added, stirred evenly, cooled and freeze-dried to prepare a Chinese herbal antibacterial agent.
2. A durable antibacterial herbal paint according to claim 1, characterized in that: The mass ratio of the wormwood essential oil to beta-cyclodextrin is 1:(0.16-0.24).
3. The durable antibacterial herbal paint according to claim 1, characterized in that: Also included are 11-15 parts of porous starch, and the preparation method of the porous starch comprises the following steps: S1, adding corn starch to a sodium chloride solution, heating and stirring evenly, adding sodium hydroxide solution to adjust the pH to 11, continuing to stir, then adding sodium trimetaphosphate and sodium hydrogen phosphate, continuing to stir, and then adjusting the pH to neutral with a hydrochloric acid solution, followed by washing, filtering, drying, and grinding to obtain sodium trimetaphosphate cross-linked corn starch; S2. Add sodium trimetaphosphate cross-linked corn starch into disodium hydrogen phosphate-citric acid buffer, preheat at a constant temperature, then add amylase to react, and finally add sodium hydroxide solution until the reaction becomes neutral. After terminating the reaction, wash and dry to obtain porous starch.
4. The durable antibacterial herbal paint according to claim 3, characterized in that: The mass ratio of the corn starch, sodium trimetaphosphate and amylase is 1:(0.12-0.16):0.
02.
5. The durable antibacterial herbal paint according to claim 3, characterized in that: Titanium dioxide is also added during the preparation of the porous starch. The preparation method of the porous starch comprises the following steps: S1, adding corn starch to a sodium chloride solution, heating and stirring evenly, adding sodium hydroxide solution to adjust the pH to 11, continuing to stir, then adding sodium trimetaphosphate and sodium hydrogen phosphate, continuing to stir, and then adjusting the pH to neutral with a hydrochloric acid solution, followed by washing, filtering, drying, and grinding to obtain sodium trimetaphosphate cross-linked corn starch; S2, adding sodium trimetaphosphate cross-linked corn starch into disodium hydrogen phosphate-citric acid buffer, preheating at a constant temperature, then adding amylase to react, and finally adding sodium hydroxide solution until the reaction is neutral, terminating the reaction, washing and drying, and obtaining primary porous starch; S3. Add a surfactant to deionized water, stir evenly, add titanium dioxide and porous starch, mix thoroughly, filter and dry in sequence to obtain porous starch.
6. The durable antibacterial herbal paint according to claim 5, characterized in that: The mass ratio of the primary porous starch to titanium dioxide is 1:(0.2-0.4).
7. The durable antibacterial herbal paint according to claim 5, characterized in that: The surfactant is sodium lauryl sulfate.
8. The durable antibacterial herbal paint according to claim 5, characterized in that: The titanium dioxide is prepared by modification, and the modification preparation method of the titanium dioxide comprises the following steps: The carbon nanotubes are added into a mixed solution of anhydrous ethanol and deionized water, and after being fully stirred, titanium dioxide is added, and then the solution is allowed to stand and age, and then dried and calcined to obtain modified titanium dioxide.
9. The durable antibacterial herbal paint according to claim 8, characterized in that: The mass ratio of the titanium dioxide to the carbon nanotubes is 1:(0.09-0.13).
10. The durable antibacterial herbal paint according to claim 1, characterized in that: The preparation method of the durable antibacterial herbal paint comprises the following steps: After the epoxy resin and ethyl acetate are evenly mixed, kaolin is added and stirring is continued. Then, the Chinese herbal antibacterial agent, dimethyl silicone oil, polyamide and hydroxyethyl cellulose are added and stirred evenly to obtain a durable antibacterial herbal coating.